The Role of Design Thinking and Technology in Innovation: A Bibliometric Analysis to Enhance Property Business Development - Hidayatulloh, Rizki (Journal of Digital Business and Innovation Management, 2025)
The property sector has undergone significant transformation through technological advancement and the strategic integration of design thinking. This paper employs bibliometric analysis to investigate the evolving intersection of technology applications and design thinking frameworks within property sector innovation. Specifically, it examines structural developments that enhance customer value, synthesizes current innovation trends, addresses practical challenges, and forecasts future trajectories. By evaluating academic contributions, thematic trends, and emerging frameworks, the study highlights how technology-enabled design thinking solutions contribute to business model innovation, product development, and user-centered approaches. The findings are intended to guide industry stakeholders in adopting sustainable innovation strategies to meet dynamic market demands. Through a bibliometric lens, this study positions design thinking and technology integration as critical mechanisms for advancing the competitiveness of the property sector.